Suspect Detection System-An Architecture Based on Surveillance Visual Analytics using IoT - Rodda, Anirudh; S, SugunaMallika; Jaiganesh, M; M, Mrunalini (International Journal of Psychosocial Rehabilitation, 2020)
In the present dayscenariothe issue of physical security is of utmost importance in any area. Providing an automated surveillance system to detectsuspicious personnel or activities withina particularvicinity with an alert feature is the need of the hour. The 21st century most prominent technology – Internet of Things (IoT) is being used in developing smart real time security surveillance systems, and providing enhanced performance and effective results by eliminating humansupervision to maximum extent. This new technology is effective both cost and storage wise. Here, the data can be transferred to a remote server such as cloud. Also, the user will be notified via e-mail after an unusual activity/movement is captured. Further, visual analytics helps to investigate the data captured and take decisions. This paper is intended to improve the understanding of related tool, technology and methodology used to design and implement such smart surveillance system systematically. In this paper, a methodology is proposed to capture the visitors’ image, identify the unknown visitors within the vicinity, storing the unknown visitors’data to the cloud server, processing the unknownvisitors’ logs and sending an e-mail notification to the security departmentof the suspicious visitor.